The Need for More Attention to The Validity and Reliability of AI-Generated Exercise Programs - Saadati, Seyed Milad (Health Nexus, 2023)
In the evolving realm of health and fitness, the integration of artificial intelligence (AI), especially tools like ChatGPT in creating exercise programs, represents a significant technological leap. This paper addresses the critical need for thorough examination of the validity and reliability of such AI-generated exercise regimens. We explore the dual facets of opportunity and challenge presented by AI in fitness, emphasizing the importance of aligning AI recommendations with established exercise science principles and individual health requirements. The paper advocates for a systematic framework to assess these programs and discusses the potential risks and benefits. Ultimately, it seeks to bridge the gap between technological innovation and health safety, promoting responsible utilization of AI to enhance physical well-being. This discussion contributes to the ongoing dialogue about AI’s role in health and fitness, underscoring the need for a balanced approach that prioritizes both innovation and safety.